MOOC as a Technology-Focused TPD for EFL Teachers in Indonesia - Anuncius Gumawang Jati (Indonesian Journal of Applied Linguistics, 2023)
This study examines participants’ expectations, perception of the learning experience, and factors contributing to satisfaction with the MOOC of a technology-focused TPD program, a professional development initiative focused on enhancing English teachers’ technology integration skills. It was participated by 200 EFL teachers in Indonesia. They were engaged in the program components such as MOOC modules, Classroom Ideas, and Community of Practice (CoP). A mixed-methods approach combined pre- and post-MOOC surveys for quantitative data collection and thematic analysis of interview data to gain deeper insights into participants’ responses. The findings indicated high participant expectations, reflecting initial interest and commitment to the program. The participants demonstrated dedication to learning and acquiring new knowledge and skills, highlighting the potential impact on learning outcomes. However, time management and internet connectivity challebges posed barriers to translating learning into practice. The CoP component was also highlighted for improvement to support the learning process better. These findings contributed to teacher professional development by offering insights for program designers and policymakers. Aligning the program with participants’ needs, providing ongoing support, and fostering collaboration could enhance the effectiveness of the MOOC of technology-focused program and promote the professional growth of English language teachers in Indonesia.